Asupan Serat Dan Magnesium Dengan Kadar Glukosa Darah Pada Pasien Diabetes Mellitus Tipe Ii - Olga Lieke Paruntu; Nonce Nova Legi; I Made Djendra; Giantri Kaligis (Jurnal GIZIDO, 2018)
Diabetes mellitus is very influential on the quality of human resources and has a significant impact on health costs. This diabetes mellitus cannot heal but can only be controlled. Patients with diabetes mellitus are not able to produce enough insulin or do not use it effectively so that there is excess glucose in the blood. One of the factors that triggers glucose is an unhealthy diet such as rarely consuming fiber, as well as consuming micronutrients, including magnesium. The general objective of this study was to determine the effect of fiber and magnesium intake with fasting blood glucose levels in type 2 diabetes mellitus patients at Pancaran Kasih General Hospital GMIM Manado. This research method using cross sectional design by purposive sampling. Data collection about the intake of fiber and magnesium using the 24-hour recall and the results of the examination of fasting blood glucose levels were taken through the medical record of the patient. Analyst data using logistic regression analysis. Based on data analysis using Fisher's Exact Test, showed P value = <0.05 / P = 0.013 means that there is a relationship between fiber intake and fasting blood glucose levels. While the results of data analysis using Fisher's Exact Test, showed P value => 0.05 / P = 0.61, meaning that there was no correlation between magnesium intake and fasting blood glucose levels. It can be concluded that there is a relationship between fiber intake and blood glucose levels. There is no relationship between magnesium intake and fasting blood glucose levels.